Parkinson’s Disease in Central Asian and Transcaucasian Countries: A Review of Epidemiology, Genetics, Clinical Characteristics, and Access to Care - Rauan Kaiyrzhanov; Mie Rizig; Akbota Aitkulova; Nazira Zharkinbekova; Chingiz Shashkin; Gulnaz Kaishibayeva; Altynay Karimova; Talgat Khaibullin; Dinara Sadykova; Manizha Ganieva; Khurshidakhon Rasulova; Henry Houlden (Parkinson's Disease)
Our understanding of Parkinson’s disease (PD) has significantly accelerated over the last few years, but predominant advances have been made in developed, Western countries. Little is known about PD in the Central Asian (CA) and Transcaucasian (TC) countries. Here, we review the clinical characteristics, treatments used, epidemiology, and genetics of PD in CA and TC countries via a methodological search in MEDLINE, EMBASE, Scopus, Web of Science, and Google Scholar databases. For the acquisition of PD care-related data, the search was extended to the local web resources. Our findings showed that PD prevalence in the region is averaging 62 per 100,000 population. The mean age of onset is 56.4 ± 2.8 in females and 63.3 ± 3.5 in males. Large-scale national studies on PD prevalence from the region are currently lacking. A limited number of genetic studies with small cohorts and inconclusive results were identified. The G2019S LRRK2 mutation, the commonest mutation in PD worldwide, was found in 5.7% of patients with idiopathic PD and 17.6% of familial cases in 153 Uzbek patients. Our review highlighted systematic deficiencies in PD health care in the region including lacks of neurologists specializing in PD, delays in PD diagnosis, absence of specialized PD nurses and PD rehab services, limited access to PD medications and surgery, and the unavailability of PD infusion therapies. Overall, this article demonstrated the paucity of data on this common neurological disorder in CA and TC countries and identified a number of healthcare areas that require an urgent consideration. We conclude that well-designed large-scale epidemiological, genetic, and clinical studies are desperately needed in this region. Healthcare professionals, local and national institutions, and stakeholders must come together to address deficiencies in PD healthcare systems in CA and TC countries.